ICU Patients Requiring Renal Replacement Therapy Initiation: Fewer Survivors and More Dialysis Dependents From 80 Years Old. Issue 8 (August 2017) - Commereuc, Morgane; Guérot, Emmanuel; Charles-Nelson, Anais; Constan, Adrien; Katsahian, Sandrine; Schortgen, Frédérique
Abstract : Objectives: To assess the role of advanced age on survival and dialysis dependency after initiation of renal replacement therapy for acute kidney injury. Design: Retrospective pooled analysis of prospectively collected data. Setting: ICUs of two teaching hospitals in Paris area, France. Subjects: One thousand five hundred thirty adult patients who required renal replacement therapy initiation in the ICU. Interventions: None. Measurements and Main Results: Survival and post acute kidney injury chronic dialysis dependency were assessed at hospital discharge according to the quintile (Q) of age. The oldest quintile included 289 patients 80 years old and over. Seventy-three percent of included patients had respiratory and hemodynamic supports at renal replacement therapy initiation, similarly distributed across quintiles. Mortality increased with age strata from 63% in Q1 (⩽ 52 yr) to 76% in Q5 (≥ 80 yr) ( p < 0.001). After adjustment, age did not increase the risk of death up to 80 years. The oldest patients (≥ 80 yr) had a significant higher risk of dying (adjusted odds ratio, 2.59; 95% CI, 1.66–4.03). Dialysis dependency was more frequent among survivors 80 years old or older (30% vs 14%; p = 0.001). Age 80 years old or older was an independent risk for dialysis dependency only for patients with prior advanced chronic kidney disease ( p = 0.04). Baseline estimated glomerular filtration rate was the only one predictor of dialysis dependency identified. Conclusions: Patients with advanced age represent a substantial subgroup of patients requiring renal replacement therapy in the ICU. From 80 years, age should be considered as an additional risk of dying over the severity of organ failures. Patients 80 years old or older are likely to recover sufficient renal function allowing renal replacement therapy discontinuation when baseline estimated glomerular filtration rate is above 44 mL/min/1.73 m 2 . At 3 months, only 6% were living at home, dialysis independent. Abstract : Supplemental Digital Content is available in the text.